Glucose-tolerant β-glucosidase retrieved from a Kusaya gravy metagenome - Uchiyama, Taku; Yaoi, Katusro; Miyazaki, Kentaro (Frontiers in Microbiology, 2015)
β-glucosidases (BGLs) hydrolyze cellooligosaccharides to glucose and play a crucial role in the enzymatic saccharification of cellulosic biomass. Despite their significance for the production of glucose, most identified BGLs are commonly inhibited by low ( mM) concentrations of glucose. Therefore, BGLs that are insensitive to glucose inhibition have great biotechnological merit. We applied a metagenomic approach to screen for such rare glucose-tolerant BGLs. A metagenomic library was created in Escherichia coli (approximately 10,000 colonies) and grown on LB agar plates containing 5-bromo-4-chloro-3-indolyl-β-D-glucoside, yielding 828 positive (blue) colonies. These were then arrayed in 96-well plates, grown in LB, and secondarily screened for activity in the presence of 10% (w/v) glucose. Seven glucose-tolerant clones were identified, each of which contained a single bgl gene. The genes were classified into two groups, differing by two nucleotides. The deduced amino acid sequences of these genes were identical (452 aa) and found to belong to the glycosyl hydrolase family 1. The recombinant protein (Ks5A7) was overproduced in E. coli as a C-terminal 6 × His-tagged protein and purified to apparent homogeneity. The molecular mass of the purified Ks5A7 was determined to be 54 kDa by SDS-PAGE, and 160 kDa by gel filtration analysis. The enzyme was optimally active at 45°C and pH 5.0–6.5 and retained full or 1.5–2-fold enhanced activity in the presence of 0.1–0.5 M glucose. It had a low KM (78 µM with p-nitrophenyl β-D-glucoside; 0.36 mM with cellobiose) and high Vmax (91 µmol min-1 mg-1 with p-nitrophenyl β-D-glucoside; 155 µmol min-1 mg-1 with cellobiose) among known glucose-tolerant BGLs and was free from substrate (0.1 M cellobiose) inhibition. The efficient use of Ks5A7 in conjunction with Trichoderma reesei cellulases in enzymatic saccharification of alkaline-treated rice straw was demonstrated by increased production of glucose.